A smoothing technique based beta finite element method (βFEM) for crystal plasticity modeling. (1st January 2016) - Zeng, W.; Liu, G.R.; Li, D.; Dong, X.W.
Highlights: A novel smoothing technique based beta finite element method ( β FEM) is proposed. The method can produce super-accurate solution and treat volumetric locking issue. A framework for large strain rate-independent crystal plasticity model is introduced. Plastic incompressibility and large mesh distortion during strain localization are tackled. The approach is further developed for modeling bi-crystal and polycrystalline plasticity. Abstract: This paper presents a novel class of smoothing techniques based beta finite element method ( β FEM) for modeling of crystalline materials. The method is first examined by a simple standard patch test and applied in elastic problems. It is then implemented to model the anisotropic plastic deformation of rate-independent single crystals and bi-crystal. Several representative examples are studied to demonstrate the capability of proposed method with the integration algorithm for capturing the strain localization and dealing with plastic incompressibility. It is also performed to simulate the mechanical behavior of polycrystalline aggregates through modeling the synthetic microstructure constructed by Voronoi tessellation technique.